2004
DOI: 10.1210/en.2004-0401
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Epidermal Growth Factor (EGF) Receptor Downstream Signaling Pathways by Betacellulin and EGF

Abstract: To determine the downstream signaling pathways regulated by betacellulin (BTC) in comparison with epidermal growth factor (EGF), we used Chinese hamster ovary cells overexpressing the human EGF receptor (ErbB1/EGFR). The overall time-dependent activation of EGFR autophosphorylation was identical in cells treated with 1 nm BTC or 1.5 nm EGF. Analysis of site-specific EGFR phosphorylation demonstrated that the BTC and EGF tyrosine phosphorylation of Y1086 was not significantly different. In contrast, the autopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 40 publications
6
51
0
Order By: Relevance
“…This difference in efficacy may reflect differences in the pattern of receptor or adapter protein phosphorylation generated by two ligands binding to the same receptor. Analogous results have been reported for the epidermal growth factor (EGF) receptor, ErbB1, where binding of EGF and betacellulin generate similar levels of ErbB1 Y1086 phosphorylation, but betacellulin produces greater Akt activation and a more robust anti-apoptotic response than EGF (47,48). Alternatively, the reduced IGF-2 FIGURE 7.…”
Section: Discussionsupporting
confidence: 71%
“…This difference in efficacy may reflect differences in the pattern of receptor or adapter protein phosphorylation generated by two ligands binding to the same receptor. Analogous results have been reported for the epidermal growth factor (EGF) receptor, ErbB1, where binding of EGF and betacellulin generate similar levels of ErbB1 Y1086 phosphorylation, but betacellulin produces greater Akt activation and a more robust anti-apoptotic response than EGF (47,48). Alternatively, the reduced IGF-2 FIGURE 7.…”
Section: Discussionsupporting
confidence: 71%
“…It has been shown that specific EGFR downstream signaling pathways can be elicited by phosphorylation on specific sites. For example, the phosphorylation of Y1068 can recruit GAB-1 or growth factor receptor-bound protein 2 (Grb-2) to activate survival signals (40), whereas the phosphorylation of Y1173 is responsible for eliciting the activation of ERK via inhibition of the SH2 domain-containing transforming protein (SHC) and Grb2 (41,42). Furthermore, the up-regulation of pY1173 also has been reported in patients who have NSCLC with EGFR mutation, and Akt, MAPK, and Stat3 signaling is higher in pY1173-positive patients (43).…”
Section: Discussionmentioning
confidence: 99%
“…The α v integrin subunit induced the phosphorylation of 845, 1068845, , 1086845, , and 1173845, (Moro et al, 2002. In addition, ionizing radiation induced phosphorylation of 992 and 1173 while betacellulin induced 1068 (Sturla et al, 2005;Saito et al, 2004). While these are major sites of phosphorylation in response to EGF, it is interesting that differential phosphorylation occurs in response to specific biologic activation.…”
Section: Discussionmentioning
confidence: 99%